Ethereum-Based Escrow System to Reduce the Risk of Peer-to-Peer Payment Abuse - Yudhistira Nanda Kumala; Rizky Parlika; Hendra Maulana (Komunitas Dosen Indonesia, 2026)
Peer-to-peer (P2P) payments facilitate rapid direct transactions but are frequently compromised by trust asymmetry, leading to substantial risks of non-delivery or non-payment. This study addresses these vulnerabilities by introducing a lightweight, deterministic escrow mechanism based on Ethereum smart contracts, specifically designed to bridge the regulatory gap in consumer protection. Unlike conventional escrow systems that rely on costly human intermediaries or complex decentralized autonomous organization (DAO) structures, the proposed